2022
DOI: 10.12968/bjom.2022.30.6.333
|View full text |Cite
|
Sign up to set email alerts
|

Practice-based learning and the impacts of COVID-19: doing it for real?

Abstract: This is the fifth article in a series exploring interprofessional education during the COVID-19 pandemic. This article focuses on the experiences and adaptations employed in relation to practice-based learning and placement provision. Forming an integral part of many professional programmes, changes in provision and approaches to practice-based learning and placements will be explored, drawing on theory and findings from existing literature and illustrated with case study reports. Opportunities for innovation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…A further welcome steer towards the integral role of practice-based learning in health care programmes and the challenges of incorporating interprofessional practice learning, that contributes to meeting the learning outcomes and competencies required for safe and effective professional practice, reported in Hutchings et al (2022), is reflected in the recent World Health Organisation (WHO) report ( 2022) which calls for competency-based learning within practice. The Global Competency Framework for Universal Health Care (World Health Organisation, 2022) reaffirms the application of knowledge, skills, attitudes, and behaviours to performance in the practice context as the means for demonstrating and assessing the mastery of learning outcomes by means of a set of defined competencies for education programmes.…”
Section: Towards Best Practice For Assessing Interprofessional Learningmentioning
confidence: 99%
“…A further welcome steer towards the integral role of practice-based learning in health care programmes and the challenges of incorporating interprofessional practice learning, that contributes to meeting the learning outcomes and competencies required for safe and effective professional practice, reported in Hutchings et al (2022), is reflected in the recent World Health Organisation (WHO) report ( 2022) which calls for competency-based learning within practice. The Global Competency Framework for Universal Health Care (World Health Organisation, 2022) reaffirms the application of knowledge, skills, attitudes, and behaviours to performance in the practice context as the means for demonstrating and assessing the mastery of learning outcomes by means of a set of defined competencies for education programmes.…”
Section: Towards Best Practice For Assessing Interprofessional Learningmentioning
confidence: 99%
“…Alguns estilos de aprendizagem exigem a presença física do educador e a interação com o aluno. Além disso, algumas pesquisas sugerem que salas de aula de baixa tecnologia podem melhorar o desempenho da aprendizagem (e.g., Barbetta & Morales, 2022;Fischer et al, 2022;Hutchings et al, 2022). Os alunos que fazem anotações manuscritas, em tese, têm melhor memória do que os alunos que fazem anotações datilografadas.…”
Section: Introdução E Metodologia De Ensinounclassified
“…The Covid-19 pandemic has caused extraordinary disruptions to the higher education landscape (Clabaugh, Duque, & Fields, 2021). It was found that there were changes and adaptation needs of students in the last two years due to the Covid-19 pandemic, such as changes in the implementation of learning in universities to online learning, where previously the learning process was carried out through face-to-face mode (Hutchings et al, 2022;Park, Kim, & Jeong, 2022;Sucu & Çakiroğlu, 2022a). Not only that, students were also faced with various demands as the learning process progressed optimally.…”
Section: Introductionmentioning
confidence: 99%